Anoxic waters constrain the vertical distribution of fish developmental stages in an oxygen minimum zone - Juan Gerardo Gutiérrez‐Bravo; Laura Sánchez‐Velasco; Sylvia Patricia Adelheid Jiménez‐Rosenberg; Mark A. Altabet; Sofia Méndez‐Mendez; Sergio Cambronero‐Solano (Limnology and Oceanography, 2024)
In the Eastern Tropical North Pacific Oxygen Minimum Zone (ETNP‐OMZ), fish larvae undergo development amidst highly variable dissolved oxygen environments. As OMZs expand, understanding the implications of low‐oxygen environments on fish development becomes increasingly relevant for fisheries management and ecosystem modeling. Using horizontal zooplankton tows to track five oxygen levels (oxic [200 μ mol/kg], hypoxic [100 μ mol/kg] suboxic [10 μ mol/kg], anoxic [ μ mol/kg], and deep [10 μ mol/kg at ~ 1000 m depth]), this study analyzed the three‐dimensional distribution of fish larvae and adults across the ETNP‐OMZ. Results revealed a wide midwater anoxic core, extending from Costa Rica to Baja California, that was almost devoid of fish larvae ( 3 ). Early larval stages primarily inhabited the oxic and hypoxic levels above the core, while postflexion and transformation stages occurred across a wider oxygen gradient, including the deep level below the anoxic core. Epipelagic species (e.g., Auxis sp.) were predominantly found in the surface oxic level, whereas coastal‐demersal species (e.g., Bregmaceros bathymaster , Ophidion spp.) were prevalent in the hypoxic level above the core. Meso‐bathypelagic species (e.g., Diogenichthys laternatus , Cyclothone spp.) were present throughout the study area, including below the anoxic core as transformation larvae and juveniles. These findings indicate that a vertical expansion of anoxic waters in OMZs could further constrain the habitat of epipelagic species, while also affecting the ontogenic vertical movements of meso‐bathypelagic species.